2019
DOI: 10.1002/cctc.201900343
|View full text |Cite
|
Sign up to set email alerts
|

Bio Adipic Acid Production from Sodium Muconate and Muconic Acid: A Comparison of two Systems

Abstract: sodium muconate and trans,trans‐muconic acid were heterogeneously hydrogenated to adipic acid, a strategic intermediate for the industry of polyamides and high performance polymers. Hydrogen pressure, metal to substrate ratio, substrate concentration and reaction temperature were varied to study the effect of these parameters on the reaction products. Commercial Pd/AC 5 % was used as catalyst and characterized by TEM, BET and XPS analyses. The results revealed that temperature is the parameter which mainly aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…[24][25][26][27][28] The latter approach is particularly attractive as MA is a bioprivileged molecule with substantial potential for diversification to commodity and specialty chemicals, as well as novel molecules for enhanced end-use properties (Scheme 1). [29][30][31] Previous work has already demonstrated the conversion of MA to an array of aliphatic commodity monomers including adipic acid and hexamethylenediamine, 24,25,[32][33][34][35][36] cyclic monomers such as εcaprolactam, 37,38 TPA and CHDA, 5,19,39,40 and novel monounsaturated compounds such as 3-hexenedioic acid and 1,4cyclohex-1/2-enedicarboxylic acid (CH1DA, CH2DA). 19,[41][42][43][44] Although the downstream production of cyclic molecules has experienced some significant advances, 39,45 the initial isomerization of biologically-produced cis,cis-muconic acid (ccMA) to Diels-Alder active trans,trans-muconic acid (ttMA) remains a major bottleneck.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27][28] The latter approach is particularly attractive as MA is a bioprivileged molecule with substantial potential for diversification to commodity and specialty chemicals, as well as novel molecules for enhanced end-use properties (Scheme 1). [29][30][31] Previous work has already demonstrated the conversion of MA to an array of aliphatic commodity monomers including adipic acid and hexamethylenediamine, 24,25,[32][33][34][35][36] cyclic monomers such as εcaprolactam, 37,38 TPA and CHDA, 5,19,39,40 and novel monounsaturated compounds such as 3-hexenedioic acid and 1,4cyclohex-1/2-enedicarboxylic acid (CH1DA, CH2DA). 19,[41][42][43][44] Although the downstream production of cyclic molecules has experienced some significant advances, 39,45 the initial isomerization of biologically-produced cis,cis-muconic acid (ccMA) to Diels-Alder active trans,trans-muconic acid (ttMA) remains a major bottleneck.…”
Section: Introductionmentioning
confidence: 99%
“…During the reaction two main intermediates, (2E)-hexenedioic acid ((2E)HxAc)) and (3E)-hexenedioic acid ((3E)HxAc)), were produced. Since the operating conditions were already optimized in a previous study [27], we decided to perform the reaction using 1% Pd PVA /AC catalysts prepared by sol-immobilization method keeping constant the reaction temperature (50 • C), hydrogen pressure (1 bar), substrate concentration (0.014 M), and metal to substrate ratio (1/200 mol Pd /mol substrate ). In this report, we show how the choice and the nature of AC support and PVA amount can affect NPs' size and the catalyst behavior, increasing the initial activity with respect to a commercial 5% Pd/AC.…”
Section: Introductionmentioning
confidence: 99%
“…Kinetic and mechanistic investigations have shown that the thermocatalytic hydrogenation of MA proceeds sequentially to produce adipic acid with near stoichiometric yields. [43][44][45][46][47] Muconic acid first undergoes 2,3-and 2,5-hydrogenations to form 2-and 3-hexenedioic acid, respectively, which are further hydrogenated to the saturated diacid (Scheme 1). The 2,3hydrogenation pathway is preferred when the reaction is performed in an organic solvent using a precious metal catalyst and H 2 gas.…”
Section: Resultsmentioning
confidence: 99%